Cuminum cyminum L.: Uses in Traditional Medicine, Methods of Propagation and Cultivation - Solexovna, Tursunova Saida; Eminjon qizi, Halimova Shoxina (American Journal of Botany and Bioengineering, 2026)
In recent years, the study of plants growing in the mountainous regions of our country has been gaining increasing popularity. For example, Cuminum cyminum L. (cumin) belongs to the Apiaceae family and has long been used as a medicinal and essential oil plant in both food and traditional medicine. The medicinal properties of this plant are so significant that they are difficult to fully comprehend. In this study, the importance of cumin in traditional medicine, its methods of propagation, and cultivation agro-technology were widely analyzed. Cumin seeds contain essential oils (cumin aldehyde, γ-terpinene, p-cymene), flavonoids, phenolic compounds, vitamins, as well as macro- and microelements. These components ensure the high biological activity of the plant. Therefore, cumin is widely used in traditional medicine as a remedy that improves digestion and possesses anti-inflammatory, antibacterial, antispasmodic, and antioxidant properties.